The SAMI Galaxy Survey: the role of disc fading and progenitor bias in kinematic transitions. Issue 2 (26th May 2021) - Croom, S M; Taranu, D S; van de Sande, J; Lagos, C D P; Harborne, K E; Bland-Hawthorn, J; Brough, S; Bryant, J J; Cortese, L; Foster, C; Goodwin, M; Groves, B; et al.
ABSTRACT: We use comparisons between the Sydney-AAO Multi-object Integral Field Spectrograph (SAMI) Galaxy Survey and equilibrium galaxy models to infer the importance of disc fading in the transition of spirals into lenticular (S0) galaxies. The local S0 population has both higher photometric concentration and lower stellar spin than spiral galaxies of comparable mass and we test whether this separation can be accounted for by passive aging alone. We construct a suite of dynamically self-consistent galaxy models, with a bulge, disc, and halo using the galactics code. The dispersion-dominated bulge is given a uniformly old stellar population, while the disc is given a current star formation rate putting it on the main sequence, followed by sudden instantaneous quenching. We then generate mock observables ( r -band images, stellar velocity, and dispersion maps) as a function of time since quenching for a range of bulge/total ( B / T ) mass ratios. The disc fading leads to a decline in measured spin as the bulge contribution becomes more dominant, and also leads to increased concentration. However, the quantitative changes observed after 5 Gyr of disc fading cannot account for all of the observed difference. We see similar results if we instead subdivide our SAMI Galaxy Survey sample by star formation (relative to the main sequence). We use EAGLE simulations to also take into account progenitor bias, using size evolution to infer quenching time. The EAGLE simulations suggest that the progenitors of current passive galaxies typically have slightly higher spin than present day star-forming disc galaxies of the same mass. As a result, progenitor bias moves the data further from the disc fading model scenario, implying that intrinsic dynamical evolution must be important in the transition from star-forming discs to passive discs.